Les traits géologiques essentiels des Andes centrales (Pérou-Bolivie) - Audebaud, Etienne (1973)
The peruano•bolivian segment of the Andes is about 2500 km long and its direction is NW-SE north of 18° S, submeridian further south. Its frame made of precambrian and hercynian folded material, constitutes a sialic basement for the Andean orogenic belt. From a stratigraphical point of view, the peruano-bolivian Andes appear as an intracratonic chain, where continental or neritic series prevail. The paleogeographic evolution is controlled by a system of two or three basins separated by rises and generally oriented parallel to the future chain; its most internal element is a high zone, where an intense volcanic activity has been remarkably constant in time and. space during the Mesozoic. The chain built up through three brief and homo•axial tectonic phases occurring respectively at the end of the Cretaceous, the end of the Eocene and the mid•Pliocene, that develop a moderate folding accompanied by large faults and by rare and local overthrusts. From one phase to the other, the concerned zone migrates progressively to the east. The magmatic evolution appears to be clearly related to the "liminal" position of the chain, that is to the existence of a subduction zone. During the upper Cretaceous and the Tertiary the intrusion of the granodioritic batholiths takes place. Their age and volume gradually decrease to the east. Then a powerful calc•alkaline volcanism sets up, the emissive centers of which migrate too in an easterly direction through the Tertiary.